2023
DOI: 10.1111/ceo.14215
|View full text |Cite|
|
Sign up to set email alerts
|

The association between keratoconus and allergic eye diseases: A systematic review and meta‐analysis

Abstract: Background To investigate the association between keratoconus (KC) and allergic eye diseases, eye rubbing, and atopy. Methods PubMed, Web of Science, Scopus, and Cochrane databases were searched for studies investigating eye allergy, atopy, and eye rubbing as risk factors for KC up to April 2021. Two authors independently screened all titles and abstracts against the predefined inclusion and exclusion criteria. The study analysed the prevalence of KC and its risk factors, including eye rubbing, family history … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 49 publications
(118 reference statements)
0
10
0
Order By: Relevance
“…16,29,30 Eye rubbing is a common physiological response to the sensation of itching and can be induced by allergy, dermatic atopy, or eczema, fatigue, and contact lenses. 3 This study showed that 48.9% of KC patients had an eye rubbing history but could not demonstrate an association between the dominant hand and a more progressed KC eye. The proportion identified here is in accordance with the CLEK studies, which reported rates of 48.2% and 50.0%, respectively.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…16,29,30 Eye rubbing is a common physiological response to the sensation of itching and can be induced by allergy, dermatic atopy, or eczema, fatigue, and contact lenses. 3 This study showed that 48.9% of KC patients had an eye rubbing history but could not demonstrate an association between the dominant hand and a more progressed KC eye. The proportion identified here is in accordance with the CLEK studies, which reported rates of 48.2% and 50.0%, respectively.…”
Section: Discussionmentioning
confidence: 54%
“…2 Although its etiology is not well defined, KC has been associated with allergies, atopic disease, eye rubbing, inheritance, and contact lens use. 3 Biomicroscopic signs include Fleischer ring Vogt striae and Munson sign as the disease progresses. 4 For patients who wear contact lenses, superficial corneal scarring is common.…”
mentioning
confidence: 99%
“…The etiology of KC remains unclear, despite numerous efforts to find a correlation with systemic diseases or environmental factors [33,34]. There is a currently unmet need for deeper understanding of the disease mechanisms, and for methods that contribute to accurate characterization of corneal properties and early detection [35,36].…”
Section: Discussionmentioning
confidence: 99%
“… 5 Seth et al observed significant associations among KC and eye rubbing, family history, and allergy, but not with allergic eye disease, atopy, asthma, and allergic rhinitis. 6 Lo et al found significant associations among KC and eye rubbing, allergic diseases, atopic diseases, asthma, atopic dermatitis/eczema, and allergic eye diseases, but not between KC and allergic rhinitis. 7 Hashemi et al showed that eye rubbing, family history of KC, allergy, asthma, and eczema were the most important risk factors for KC.…”
mentioning
confidence: 99%
“…Ocular itching is the pathognomonic symptom of allergic conjunctivitis (AC), one of the most common allergic conditions worldwide. 10 Although the prevalence of AC in patients with KC, 6 9 , 11 the effect of AC on corneal biomechanics, 12 , 13 as well as the effect of AC on KC severity 14 , 15 have been investigated extensively, a comparative analysis of tear fluid factors between AC and KC has never been performed before, to our knowledge. Studies comparing patients with KC, or AC, to healthy controls (HCs) have identified a number of notable protein biomarkers present in both conditions.…”
mentioning
confidence: 99%